Switchable Ring‐Opening Polymerization by a Ferrocene Supported Aluminum Complex. Issue 16 (6th August 2019) - Lai, Amy; Hern, Zachary C.; Diaconescu, Paula L.
Abstract: An aluminum(III) iso ‐propoxide complex supported by salfen (1, salfen=1, 1′‐di(2, 4‐bis‐ tert ‐butyl‐salicylimino)ferrocene) was synthesized and characterized. Compound 1 can be reversibly oxidized and reduced, and both redox species were surveyed as ring‐opening polymerization catalysts for cyclic esters and cyclohexene oxide. Based on the observed reactivity behavior, 1 could be used as a redox‐switchable catalyst for the formation of AB and ABC type di‐ and triblock copolymers of lactide, cyclohexene oxide, and trimethylene carbonate. Abstract : Switch it on : A redox‐switchable ferrocene‐supported aluminum complex is investigated as a ring‐opening polymerization catalyst. The sequential addition of chemical redox reagents and monomers changes the selectivity and activity of the catalyst. AB and ABC type block copolymers were synthesized from L‐lactide, cyclohexene oxide, and trimethylene carbonate and were characterized by NMR spectroscopy, DOSY, and SEC.